Marketing strategies of the female-only gym industry: A case-based industry perspective - Wang, Fong-Jia; Hsiao, Chia-Huei; Hsiung, Tao-Tien (Frontiers in Psychology, 2022)
Female customers are an important market for fitness centers. This study aims to examine successful fitness training health models used by female fitness clubs. A case study approach and the interview method were used to collect data (i.e., face-to-face interviews) regarding the marketing strategies of female fitness clubs. Purposive sampling was employed to select executives working at the headquarters of a female-only gym, and semi-structured interviews were conducted to provide a context for fitness behaviors and to discuss the business’ marketing mix. Six managers at Curves (four female and two male) across six different positions were interviewed. This study found that Curves’ most significant difference compared to other private fitness clubs is that it makes women feel comfortable. Through charitable activities combined with promotions, women feel as if the gym empathizes with them. This study is unique in that it is one of the first studies to explore the business model of the female fitness club. In particular, this research suggests that sports organizations should focus their services strategies on female exercise demands. The findings of this study will support the development of marketing strategies to promote the growth of women’s health as a priority within the fitness industry.